Orphanhood, Poverty and the Care Dilemma: Review of Global Policy Trends - Tatek Abebe (Social Work and Society, 2009)
The care and protection of children experiencing orphanhood presents a major child-care policy challenge. This paper draws on a review of the literature to document divergent conceptualizations of orphanhood, how the hurdles for the care of orphans reflect wider issues of poverty and inequality, as well as the ways in which different care interventions (familial, institutional, community-based and rights-based) might be appropriated for children in need. It is argued that the map of contemporary orphanhood overlaps with the contours of global poverty, inequality, age-based deprivations and marginalization. An example of a 'globalised' model of orphan care, namely SOS Children's Villages, is presented and its implications for policy are examined. The paper highlights the significance of fighting poverty and enhancing the care-giving capabilities of extended families in the care and protection of children from a rights-based perspective. It suggests that external interventions should primarily address the structural causes of poverty and marginality, rather than amplifying inequalities through the selective support of orphans in economically vulnerable communities.